A mixed source for the Late Triassic Garzê-Daocheng granitic belt and its implications for the tectonic evolution of the Yidun arc belt, eastern Tibetan Plateau - Wu, T.; Xiao, L.; Wilde, Simon; Ma, C.; Zhou, J. (Elsevier BV, 2017)
Many Late Triassic granitic plutons are present in the eastern Yidun arc belt (EYAB), and seven have been investigated in this study. From west to east, they are: the Sucuoma (235 ± 2 Ma), Ajisenduo (224 ± 2 Ma), Jiaduocuo (218 ± 1 Ma), Cuojiaoma (219 ± 1 Ma), Maxionggou (225 ± 2 Ma), Dongcuo (222 ± 3 Ma) and Daocheng (220 ± 2 Ma) plutons. Most of the plutons have granitic compositions and contain high SiO 2 , Al 2 O 3 and K 2 O + Na 2 O, but low MgO, FeO* and CaO contents. They have similar trace element patterns, with depletion in high field strength elements (HFSE, e.g., Nb and Ta) and enrichment in large-ion lithophile elements (LILE, e.g., Rb, Th and U). Samples from the Sucuoma, Jiaduocuo and Dongcuo plutons have similar zircon Hf isotopic compositions (e Hf (t) = - 1.8 to - 0.3, - 3.1 to 0.4 and - 4.6 to - 1.4, respectively), whereas those from the Ajisenduo pluton exhibit more unradiogenic Hf (e Hf (t) = - 11.9 to - 4.8). Additionally, the Sucuoma pluton has the lowest initial 87 Sr/ 86 Sr values (0.7060–0.7090) but the least negative e Nd (t) (- 4.9 to - 3.3) values, whereas samples from the Ajisenduo pluton have the highest initial 87 Sr/ 86 Sr values (0.7111–0.7160), but the most negative e Nd (t) values (- 7.9 and - 11.3). All the samples have similar high radiogenic Pb isotopic compositions ( 206 Pb/ 204 Pb = 18.6–19.4; 207 Pb/ 204 Pb = 15.7–15.8; 208 Pb/ 204 Pb = 39.1–40.4). Based on the new geochemical data, it is determined that most of the granitoids are I-type granites and the magma source was a mixture of the metamorphic Kangding Complex, which is considered to be the basement of the western Yangtze Craton, and metasediments from the basement. However, the samples from the Ajisenduo pluton are S-type granites that were derived from partial melting of basement metasediments with only limited components from the Kangding Complex. Together with an evaluation of previously-published work, these new data indicate a dominant magmatic peak at ca. 216 Ma for the Late Triassic granitoids of the YAB and that the ages of Late Triassic magmatism become younger eastward towards the Garzê-Litang suture zone. We consider that slab roll-back, with subsequent slab break-off, best explains the origin of these granitic plutons.